EVOLVING A PSHYCOMETRIC INSTRUMENT TO MEASURE WORK LIFE BALANCE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Education industry is a big contributor in  Indian service sector in terms of providing  employment and eventually contributes to  the factor determining national GDP. In the  continuation, issues and challenges related to  Work life balance have been gaining attention  as well. These issues have been observed to be  more prominent in service sector.  However, various researchers and studies  have developed few scales to measure work  life balance but current study is an attempt  to define a much elaborative and precise scale  for the measurement of WLB in education  industry. In present work, a 30 items scale  defined under three factors is designed to  measure WLB of academicians working  in education industry. The data for the  purpose was collected from a sample of 125  academicians working in private universities  in Jaipur City. The reliability and validity of  the scale has been tested by using Cronbach  Alpha analysis.
Keywords: Work-life balance; psychometric; education industry